CONSIDERATIONS CONCERNING PUBLIC PENSION SYSTEM - Emilia CLIPICI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The article addresses a topical theme at national and European level, approaching the social security scope in the context of the economic development of the globalization of the phenomena and processes on the labour market, as well as the demographic perspectives correlated to the other influencing factors. Today, in the budgets of all European countries, the pension spending is a burdening chapter, increasingly difficult to support.